Correspondencia entre la ley orgánica de comunicación LOC vigente y el ejercicio periodístico en el Ecuador en el año 2017 - Reyes Gracia, Stives Oswaldo (2019)
Since its approval in 2013, the Organic Law of Communication (LOC) containing 113 articles, has been the focus of discussion, criticism, debates, approvals, etc. by the media and journalists of Ecuador. In this investigation we focus only on two articles that arises the LOC: The 18 and the 26 that deal with the previous censorship and the media lynching, because as graduates of the career of Journalism we believe that they would be attacking the principle of freedom of expression. That is why we developed an analysis with the different points of view of journalists in the political section of Diario Expreso, El Comercio, El Universo and El Telégrafo in Guayaquil, Quito and Cuenca, together with their editors, in which we established problems and consequences which causes in the journalistic exercise the execution of the aforementioned articles, by means of surveys and interviews as collection techniques where we obtained more accurate and precise answers from those who currently practice the journalism profession……….